Предмет: Математика,
автор: irinakholod
Упростить и вычислить: А) 8(2x + 4) – 4(3x –1) при х= 3; х = -4 Б) 4(6a -8b + 3c) - 7(6a + 5b – c) при а= 2, в =-1; с= 4
Ответы
Автор ответа:
0
А) 8(2х+4)-4(3х-1) при х=3; х= - 4
1. Упрощаем
8(2х+4)-4(3х-1)=16х+32-12х+4=4х+36
2. Вычисляем.
4х+36 при х=3; х= - 4
а) 4х+36 при х=3
4×3+36=12+36=48
Ответ: 48
б) 4х+36 при х= - 4
4×(-4)+36= - 16+36=20
Ответ: 20
Б) 4(6а-8b+3c)-7(6a+5b-c) при а=2; в= - 1; с=4
1. Упрощаем.
4(6а-8b+3c)-7(6a+5b-c)=24a-32b+12c-42a-35b+7c= - 18a-67b+19c
2. Вычисляем.
- 18а-67b+19c при а=2; b= - 1; c=4
a) - 18×2-67×(-1)+19×4= - 36+67+76=31+76=107
Ответ: 107
Вот правильное решение!
Сверху неправильно решение!
1. Упрощаем
8(2х+4)-4(3х-1)=16х+32-12х+4=4х+36
2. Вычисляем.
4х+36 при х=3; х= - 4
а) 4х+36 при х=3
4×3+36=12+36=48
Ответ: 48
б) 4х+36 при х= - 4
4×(-4)+36= - 16+36=20
Ответ: 20
Б) 4(6а-8b+3c)-7(6a+5b-c) при а=2; в= - 1; с=4
1. Упрощаем.
4(6а-8b+3c)-7(6a+5b-c)=24a-32b+12c-42a-35b+7c= - 18a-67b+19c
2. Вычисляем.
- 18а-67b+19c при а=2; b= - 1; c=4
a) - 18×2-67×(-1)+19×4= - 36+67+76=31+76=107
Ответ: 107
Вот правильное решение!
Сверху неправильно решение!
Автор ответа:
0
дайте балл
Похожие вопросы
Предмет: Геометрия,
автор: abilkasimdiar
Предмет: Информатика,
автор: lveronika083
Предмет: Физика,
автор: daria140220
Предмет: Биология,
автор: mimoza17
Предмет: Математика,
автор: adidas52